2015
DOI: 10.1017/s1366728915000103
|View full text |Cite
|
Sign up to set email alerts
|

Cross language lexical priming extends to formulaic units: Evidence from eye-tracking suggests that this idea ‘has legs’

Abstract: Idiom priming effects (faster processing compared to novel phrases) are generally robust in native speakers but not non-native speakers. This leads to the question of how idioms and other multiword units are represented and accessed in a first (L1) and second language (L2). We address this by investigating the processing of translated Chinese idioms to determine whether known L1 combinations show idiom priming effects in non-native speakers when encountered in the L2. In two eye-tracking experiments we compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
6
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 64 publications
9
95
6
6
Order By: Relevance
“…First of all, the terminal word of our items received shorter fixations when they were part of an idiom as opposed to part of a phrase. This replicates an effect that has previously been observed in English idioms (see Underwood, Schmitt, & Galpin, 2004) and translated Chinese idioms (see Carrol & Conklin, 2015). Furthermore, idioms as a whole received shorter gaze durations than phrases, an effect that has also previously been observed in English (Siyanova-Chanturia, Conklin, & Schmitt, 2011).…”
Section: Chinese Idiom Processingsupporting
confidence: 86%
See 1 more Smart Citation
“…First of all, the terminal word of our items received shorter fixations when they were part of an idiom as opposed to part of a phrase. This replicates an effect that has previously been observed in English idioms (see Underwood, Schmitt, & Galpin, 2004) and translated Chinese idioms (see Carrol & Conklin, 2015). Furthermore, idioms as a whole received shorter gaze durations than phrases, an effect that has also previously been observed in English (Siyanova-Chanturia, Conklin, & Schmitt, 2011).…”
Section: Chinese Idiom Processingsupporting
confidence: 86%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w O n l y One prior study has used eye-tracking methodology to examine the processing of Chinese idioms. Carrol and Conklin (2015) presented four-character Chinese idioms, which were translated into English, to bilingual native Chinese speakers. It was found that the final word of these translated idioms received shorter fixations than the final word of a matched phrase.…”
Section: More Recently Cutter Drieghe and Liversedge (2014) Demonstmentioning
confidence: 99%
“…This makes our account task-dependent in the light of timing differences between research paradigms. In many studies, it is the sentence-final word that is the focus of investigation (e.g., Carrol & Conklin, 2017; Carrol et al, 2016, Rommers et al, 2013). When this word is processed, both the idiomatic sentence interpretation and the literal sentence intepretation are still under development.…”
Section: Task Aspectsmentioning
confidence: 99%
“…The final paper is by Carrol and Conklin (2017), who focus on cross-linguistic priming in the processing of idioms in Chinese–English bilinguals. Based on two eye-tracking experiments in which bilinguals read English sentences that contained Chinese idioms (translated in English), they find that idioms modulate reading times, and that figurative meanings of the idioms are processed slower than literal meanings.…”
mentioning
confidence: 99%